Comunicação e cultura na internet: em busca de outros jornalismo culturais - Alzamora, Geane Carvalho (2005)
This research begins with the following questions: which language and cultural features shapes cultural webjournalism and to what extent the later is different from the classical model of cultural journalism in the mass media? To answer these questions, we tried initially to characterize the episthemological realm of the cultural journalism, from a historical perspective which would deal with his language evolution and cultural approaching. Press journalism is taken as a comparative reference because it created the classical model of cultural journalism built by the twentieth century mass media and so it has been a beacon for most of the internet journalistic experiences. The social apropriation of the internet has meaned a new communcational logic, based on contribution, participation and sharing of socially produced informations. The hipermidiatic communication logic is heightened by the media language resources, like multimidiality, hypertextuality, interactivity and memory. On the other hand, the mass logic is characterized by the transmission of information from the basis of centralized social mediations. This transmissive logic has been analysed with mass communication theories and models, and later it has been contrasted, through the peircean semiotics model, with the associative logic of the hypermidiatic communication. Determination and representation semiotic operations, which complete themselves in the semiotic or mediation operation, were related, respectively, to the transmissive logic and to the communicational associative logic. Semiotics suppose continuous improvement of signical processes. On the same way, journalistic semiotics seems to point out to a broadening of its communicational logic, as demonstrated by the new ways of internet cultural information. To investigate the formats through which cultural information circulate on the internet, it has been created a virtual community to discuss, between 2002 and 2004, this issue. Simultaneously, an FCA/PUCMinas and UNI-BH research staff discussed and referenced, in a website, some paradigms of circulation of cultural information on internet. Then, the referenced websites were analysed with the peircean semiotics model focus, and it was measured to what extent they get closer or move away from the cultural journalism classical model. The results has shown that hybridism reigns on the net and that this fact perhaps require the broadening of the cultural journalism concept with the aim of embracing the specificities of hypermidiatic communication associative logic